PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR TEMATIK SISWA SEKOLAH DASAR - Arifin, Muhammad Nurul; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is "What is the effect of mind mapping models on learning outcomes in students' thematic learning in class V of South Pontianak 36 Primary School?". This study aims to examine how much influence the Mind Mapping Model has on the learning outcomes of Grade V students of 36 Primary Schools in South Pontianak. The method used is experimental, while the form of research used is quasi experimental design with nonequivalent control group design. The population in this study were all fifth grade students at 36 Pontianak Elementary School in South Pontianak. Data collection tools used in the form of Multiple Choice tests totaling 50 questions. Based on statistical calculations, the average results of the experimental class post-test was 78.20 while the average post-test results of the control class were 72.00. T test results obtained t count = 2,356 and t table Î± = 5% (with dk = 25 + 26 - 2 = 49) of 1,683, which means t count (2,356)> t table (1,683), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is an effect of the mind mapping model on learning outcomes in the thematic learning of fifth grade students at 36 elementary schools in South Pontianak. The result of the calculation of the effect size (ES) was 0.59 which was classified as medium criteria so that the mind mapping model had a good influence on the learning outcomes of the fifth grade students of 36 Pontianak Elementary School.Keywords: Mind Mapping Model, Learning Outcomes, Thematic Learning.